TEACHING ENGLISH USING MONTESSORI METHOD TO INCREASE STUDENT’S VOCABULARY: AN ACTION RESEARCH IN TKIT AL-FARISI MAJALENGKA IN 2006/2007 ACADEMIC YEAR - SUSILA , SUSI TRI (2007)
This study aims at describing the process of teaching vocabulary using Montessori Method at Al Farisi Kindergarten, the result and the advantages and the weaknesses of it. Classroom Action Research (CAR) was done in TKIT Al-Farisi Majalengka. The writer took the students of class B (Khadijah class) of TKIT Al Farisi Majalengka in 2006/2007 Academic Year as the subject of the study, whose ages are 5-6 years old. The writer conducted the treatment to the students in the form of pre- test and post-test. After collecting the data and analyzing them by using classroom action research, the writer described the result of the research. She found that there were three kinds of the result in the research: (1) there were 14 students (73, 68%) who increased the vocabulary achievement (2) there were 3 students (15, 79 %) who decreased their vocabulary achievement (3) there were 2 students (10, 53 %) who are static or did not develop their vocabulary achievement. The conclusion is teaching vocabulary using Montessori Method at TKIT Al- Farisi Majalengka yields good and effective result. There is some strength that can be found in vocabulary class, (1) the students have a high interest in following teaching- learning process. (2) the students are motivated to be active in the class. (3) it is easy to understand, memorize, remember, and it can avoid misunderstanding because the students see the picture and use it in playing the games. Besides, there are also some weaknesses of it, the teachers should spend their time, money and energy to teaching English using Montessori Method.